PENGARUH KREATIVITAS DAN PENGETAHUAN MANAJEMEN TERHADAP MINAT BERWIRAUSAHA MAHASISWA (STUDI KASUS PADA MAHASISWA UNIVERSITAS TANJUNGPURA) - Anggit, Annisa Anggit Nofrida Batubara B1021151032 (Jurnal Manajemen Update, 2019)
ABSTRACTAlmost in every developed country, the standard has population of entrepreneur of more than 14%, while the country of Indonesia is still at 3,1% which means that it is necessary to increase the number of entrepreneurs to further boost Indonesia’s economy. There are many factors that cause the number of our entrepreneurs to be still small, one of which is the orientation of most of the graduates of Higher Education as job seekers job seekers compared to the creator of employment job creator. This study aims to find out and analyze whether the creativity and knowledge of management influence the interest in entrepreneurship at Tanjungpura University students. Sampling uses the Purposive Sampling method, with a total sample of 99 students. The analytical method used is Multiple Linear Regression Analysis using SPSS 23. The results of this study are that creativity has a significant and positive effect on the interest in college student entrepreneurship and management knowledge has a significant and positive effect on the interest in student entrepreneurship. With the independent variable contribution of 28.5%, while the remaining 71.5% is influenced by other variables not examined in this study.Keywords: Creativity, Knowledge Management, Entrepreneurship Interested.Daftar PustakaAlma, Buchari. (2011). Kewirausahaan. Bandung: Alfabeta.Azhari., Musnadi, S., & Tabrani, M. (2017). Pengaruh Manajemen Pengetahuan, Gaya Kepemimpinan dan Insentif Terhadap Kinerja Pegawai Serta Implikasinya Terhadap Kinerja Organisasi pada Kantor Pelayanan Pajak Pratama Banda Aceh. Jurnal Manajemen dan Inovasi. Vol. 8, No. 2.Badan Pusat Statistik Indonesia 2017Badan Pusat Statistik Indonesia 2018Badan Pusat Statistik Kalimantan Barat Tahun 2018.Citradewi, A., & Margunami. (2016). Pengaruh Kepribadian, Pendidikan Kewirausahaan, dan Lingkungan Keluarga Terhadap Aktivitas Berwirausaha Mahasiswa Universitas Negeri Semarang. Econonic Education Analysis Journal.Vol 5. No.2. (p-ISSN 2252-6544) (e-ISSN 2502-356X).Daft, Richard L. (2012). Era Baru Manajemen. Jakarta: Salemba Empat.Fillis, I.R., & Rentschler, R., (2010). The Role of Creativity in Entrepreneurship. Journal of Entrepresing Culture. 10.1142.Ghozali, Imam. (2011). Aplikasi Analisis Multivariat dengan Program SPSS. Semarang: Badan Penerbit Universitas Diponegoro.Hasibuan, M. (2011). Manajemen: Dasar, Pengertian, dan Masalah. Jakarta: Bumi Aksara.Hendrawan, S.J., & Sirine, H. (2017). Pengaruh Sikap Mandiri, Motivasi, Pengetahuan Kewirausahaan Terhadap Minat Berwirausaha (Studi Kasus pada Mahasiswa FEB UKSW Konsentrasi Kewirausahaan). Asian Journal of Innovation and Entrepreneurship.Vol 2, (e-ISSN: 2477-0574) ; (p-ISSN: 2477-3824).Hendri, M. I., Rochayati, I., & Fahmi, M. (2015). Desain Pengembangan Aktivitas Kemahasiswaan dengan Pendekatan Psychological Capital dalam Meningkatkan Minat dan Kemampuan Berwirausaha Mahasiswa Fakultas Ekonomi UNTAN.Jurnal Ekonomi Bisnis dan Kewirausahaan.Vol 4, 211-227.Kasmir. (2012). Kewirausahaan Edisi Revisi. Jakarta: PT. Raja Grafindo Persada.Kristanto, H. C. R. Heru. (2009). Kewirausahaan. Yogyakarta: Graha Ilmu.Kandou, Y. L., Lengkong, V.P.K., & Sendow, G. (2016). Pengaruh Knowledge Management, Skill, dan Attitude Terhadap Kinerja Karyawan (Studi Pada PT. Bank Sulutgo Kantor Pusat di Manado). Jurnal Berkala Ilmiah Efisiensi. Vol. 16. No. 01.Mar, M. D., Minano, C., & Campo, D. C. (2017). The Role of Creativity in Entrepreneurship: an Empirical Study on Business Undergraduates.Mertayasa, I, P, N.,Agustini, K., &Divayana, D, G, H. (2017). Hubungan Knowledge Management Terhadap Kreativitas Mahasiswa JurusanMayasari, T., Kadarohman, A., & Rusdiana, D. (2013). Eksplorasi Dimensi Kreativitas Untuk Pengembangan Produk Kreatif Energi Baru dan Terbarukan. Jurnal Pengajaran MIPA. Vol. 18 No. 2. 221-229.Nitisusastro, M. (2012). Kewirausahaan dan Manajemen Usaha Kecil. Bandung: Alfabeta.Pendidikan Teknik Informatika Undiksha Singaraja. KARMAPATI. Vol 6, No. 1. 2252-9063.Puspitaningtyas, Z. (2017). Pengaruh Efikasi Diri dan Pengetahuan Manajemen Keuangan Bisnis Terhadap Intensi Berwirausaha. Jurnal Wira Ekonomi Mikroskil. Vol 7, No 02. 141-150.Puryantini, N., Arfati, R., & Tjahjadi, B. (2017). Pengaruh Knowledge Management Terhadap Kinerja Organisasi Dimediasi Inovasi di Organisasi Penelitian Pemerintah. Berkala Akuntansi dan Keuangan Indonesia. Vol. 02 No. 02. 21-38Rianto, S & Al Banin, Q. (2015). Pengaruh Pengetahuan Manajemen Mahasiswa Terhadap Intensi Berwirausaha yang Dimoderasi Oleh Kecerdasan Emosional dan Kecerdasan Spiritual. STIE Islam Bumiayu, Indonesia.Rhodes, Mel. (1961). An Analysis of Creativity. The Phi Delta Kappan. Vol 42. No 7. 305-310.Ridhotullah, S. & Jauhar, M. (2015). Pengantar Manajemen. Jakarta: Prestasi Pustakarya.Sari, F.N. (2016). Pengaruh Pendidikan Kewirausahaan, Kreativitas, dan Motivasi Berwirausaha Terhadap Minat Berwirausaha Pada Mahasiswa Pendidikan Ekonomi Universitas Kanjuruhan Malang.Siagian, F L. (2017). Pengaruh Pengetahuan Manajemen Mahasiswa Terhadap Minat Berwirausaha yang Didasari Oleh Kecerdasan Emosional. Politeknik Bisnis Indonesia. Vol. 7 No. 2 Agustus 2017.Slamet, F., Tunjungsari, H.K., & Le, M. (2014). Dasar-dasar Kewirausahaan. Jakarta: PT. Indeks Permata Putri Media.Sopandi, O.D. (2016). Implementasi Knowledge Management pada Perguruan Tinggi. Jurnal Administrasi Pendidikan. Vol. XXIII No. 2.Sugiyono. (2008). Metode Penelitian Bisnis (Pendekatan Kuantitatif, Kualitatif, dan R&D. Bandung:Alfabeta.Sugiyono. (2011). Metode Penelitian Kuantitatif, Kualitatif, dan R&D. Bandung: Alfabeta.Sugiyono. (2014a). Metode Penelitian Manajemen. Bandung: Alfabeta.Sugiyono. (2014b). Metode Penelitian Kuantitatif, Kualitatif, dan R&D. Bandung: Alfabeta.Sule, E.T., & Saefullah, K. (2010). Pengantar Manajemen. Jakarta: Kencana.Sule, E.T., & Saefullah, K. (2018). Pengantar Manajemen. Jakarta: Prenamedia Group.Suryana. (2003). Kewirausahaan: Pedoman Praktis, Kiat & Proses Menuju Sukses Jakarta: Salemba Empat.Suryana. (2013). Ekonomi Kreatif, Ekonomi Baru: Mengubah Ide & Menciptakan Peluang. Jakarta: Salemba Empat.Wijayanti, D.P., & Sundiman, D. (2017). Pengaruh Knowledge Management Terhadap Kinerja Karyawan (Studi Empiris Pada PTR. SMS Kabupaten Kotawaringin Timur). DeReMa Jurnal. Vol. 12 No. 1.Wulandari, P.H. (2018). Pengaruh Kreativitas dan Hasil Belajar Terhadap Minat Berwirausaha pada Siswa Kelas XI Tata Niaga SMK Negeri 1 Kota Jambi.